Effect of blood pressure variability in the randomized controlled BP TARGET trial. (17th December 2021) - Maïer, Benjamin; Gory, Benjamin; Lapergue, Bertrand; Sibon, Igor; Escalard, Simon; Kyheng, Maeva; Labreuche, Julien; de Havenon, Adam; Petersen, Nils; Anadani, Mohammad; Gayat, Etienne; Boursin, Perrine; et al.
Abstract: Background and purpose: The Blood Pressure Target in Acute Ischemic Stroke to Reduce Hemorrhage After Endovascular Therapy (BP TARGET) trial evaluated whether an intensive systolic blood pressure (SBP) target resulted in reduced rates of intracranial hemorrhage (ICH) after successful endovascular therapy (EVT) but did not assess the effect of blood pressure variability (BPV) on functional outcomes and ICH occurrence. We sought to evaluate this question in the BP TARGET trial. Methods: We performed a post hoc analysis of the BP TARGET trial and included patients with at least 50% of blood pressure (BP) recordings during the first 24 h after EVT. BPV parameters were SBP and diastolic BP (DBP) coefficient of variation (CV), standard deviation (SD), maximum–minimum (max–min), successive variation (SV), and time rate. The primary outcome was favorable functional outcome (3‐month modified Rankin Scale between 0 and 2); the secondary outcome was the rate of ICH at 24 h. Results: We included 290 patients (mean number of BP measures = 30.4, SD = 8.0). BPV parameters (SBPSD, SBPmax–min, SBPCV ) were higher in the intensive SBP target group. Only DBP BPV parameters were associated with worse functional outcomes in the unadjusted model (DBPSD, DBPmax–min, DBPCV, and DBPSV ), but not after adjustment. Higher SBPmax–min was associated with worse functional outcomes in Thrombolysis in Cerebral Infarction 2B patients (odds ratio [OR] = 0.62, 95% confidence interval [CI] = 0.38–1.02), but not in patients with complete reperfusion (OR = 1.27, 95% CI = 0.80–2.02, p for heterogeneity (p het =0.037). None of the BPV parameters was associated with ICH, regardless of the randomization group or the reperfusion grade. Conclusions: BPV was significantly higher in the intensive SBP target group but was not associated with functional outcome or ICH. Abstract : To date, current European guidelines suggest that neurologists should monitor blood pressure (BP) noninvasively and not actively reduce systolic BP to <130 mmHg during the first 24 h after successful endovascular therapy (EVT). The present findings also suggest against BP fluctuation, notably by the intermittent use of bolus, discontinuation, and reinitiation of intravenous antihypertensive treatments such as nicardipine. Finally, further analyses are needed to clarify the impact of BP management according to the reperfusion status. Current guidelines do not suggest a distinction based on the specific reperfusion status (i.e., Thrombolysis in Cerebral Infarction 2B vs. 3) regarding BP management after successful EVT.